Palmitic Acid: Physiological Role, Metabolism and Nutritional Implications - Carta, Gianfranca; Murru, Elisabetta; Banni, Sebastiano; Manca, Claudia (Frontiers in Physiology, 2017)
Palmitic acid (PA) has been for long time negatively depicted for its putative detrimental health effects, shadowing its multiple crucial physiological activities. PA is the most common saturated fatty acid accounting for 20-30% of total fatty acids in the human body and can be provided in the diet or synthesized endogenously via de novo lipogenesis (DNL). PA tissue content seems to be controlled around a well-defined concentration, and changes in its intake do not influence significantly its tissue concentration because the exogenous source is counterbalanced by PA endogenous biosynthesis. Particular physiopathological conditions and nutritional factors may strongly induce DNL, resulting in increased tissue content of PA and disrupted homeostatic control of its tissue concentration. The tight homeostatic control of PA tissue concentration is likely related to its fundamental physiological role to guarantee membrane physical properties but also to consent protein palmitoylation, palmitoylethanolamide (PEA) biosynthesis, and in the lung an efficient surfactant activity. In order to maintain membrane phospholipids (PL) balance may be crucial an optimal intake of PA in a certain ratio with unsaturated fatty acids, especially PUFAs of both n-6 and n-3 families. However, in presence of other factors such as positive energy balance, excessive intake of carbohydrates (in particular mono and disaccharides), and a sedentary lifestyle, the mechanisms to maintain a steady state of PA concentration may be disrupted leading to an over accumulation of tissue PA resulting in dyslipidemia, hyperglycemia, increased ectopic fat accumulation and increased inflammatory tone via toll-like receptor 4. It is therefore likely that the controversial data on the association of dietary PA with detrimental health effects, may be related to an excessive imbalance of dietary PA/PUFA ratio which, in certain physiopathological conditions, and in presence of an enhanced DNL, may further accelerate these deleterious effects.